(untitled) (Scientific journal of the Fergana State University, 2024)
The paper discusses the production of carbon adsorbents based on carbon raw materials and their physicochemical properties. One of the urgent tasks is to further improve methods and technologies for the production of carbon adsorbents based on carbon-containing raw materials. For this purpose, the production of carbon adsorbents from waste of local tree trunks, including waste from poplar and willow, is of particular importance. General information about these raw materials is presented in the studies conducted. A significant decrease in weight, corresponding to a sharp change in the weight loss curve, was observed for both types of raw materials at temperatures of 210-300°C. A sharp decrease in mass occurred up to 500°C, and at this temperature it is clear that the highest rates of decomposition of organic matter in secondary raw materials are observed, and the mass loss is about 60-70%. It was found and discussed that the moisture content of the samples was 3.5-5% and the ash content was 6-8%. It is of practical importance that the production of carbon adsorbents is productive, and the amount of moisture and ash meets the requirements for carbon adsorbents.